Resources Availability and Income Achievement: a Driving Force for Competitiveness of Rice Farming Products in Tidal Land, South Sumatera, Indonesia - Adriani, Dessy; Purbiyanti, Erni; Sari, Serly Novita; Huanza, M.; Damayanthy, Dini; Sulastri, Merna Ayu (Jurnal AGRISEP, 2024)
The land conversion of rice farming could only be prevented by increasing farming competitiveness. The first step is to map the resource availability supporting paddy farming and income achievement. Therefore, this study aimed to analyze resource availability and income achievement to increase paddy business competitiveness. It used a survey method and observed two populations of farmers producing paddy seed and rice in Tanjung Lago and Rambutan Districts, Banyuasin Regency. Simple random sampling was adopted to determine 130 respondents from two populations, each with 65 rice and paddy seed farmers. The findings showed that resource availability supports farming in tidal land, though it is significantly higher for paddy seed than rice farmers. Regarding income achievements, paddy seed farmers also have higher R/C and B/C values than rice farmers. Income for rice farmers mainly comes from corn, rubber, and oil palm, while paddy seed farmers earn from their farming. This implies that the chance of land conversion into plantations and corn farming is greater for rice than for paddy seed farmers. When this happens on a large scale and in the long term, it impacts national rice production. Therefore, improved resource availability and better integration in production could sustainably increase paddy farming production in tidal land.